Un eveniment însemnat din viaţa Mitropoliei Clujului, Maramureşului și Sălajului: Sfinţirea Bisericii „Sfântul Prooroc Ilie Tesviteanul” din Cluj-Napoca - Rojneac, Vasile (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2019)
This evocation emphasizes an important event in the life of Vad, Feleac and Cluj Diocese, namely: the consecration of the Church „Saint Prophet Elijah” from the Cluj district Mărăşti, located on Târnavelor Street, no. 4. The consecration service took place on October 19, 2019, being officiated by His Eminence Metropolitan Andrei Andreicuţ, surrounded by a council of priests and in the presence of many believ- ers from Cluj-Napoca. The construction of this church began in 1984, with theconsentofthecommunistauthorities,andrequired35years of continuous work.